Trajectory statistics and turbulence evolution. (December 2015) - Vlad, M.; Spineanu, F.
Abstract: The aim of this paper is to understand the tendency to organization of the turbulence in two-dimensional ideal fluids. A different perspective on vorticity separation and on the inverse cascade of energy yields from this study. Trajectory trapping or eddying appears to be strongly connected to these nonlinear processes. The statistics of the trajectories of the vorticity elements in a turbulent state is studied using a semi-analytic method. We show that the separation of the positive and negative vorticities is due to the attraction produced by a large scale vortex on the small scale vortices of the same sign. More precisely, a large scale velocity is shown to determine average transverse drifts, which have opposite orientations for positive and negative vorticity. They appear only in the presence of trapping and lead to energy flow to large scales due to the increase of the circulation of the large vortex. Recent results on drift turbulence evolution in magnetically confined plasmas are discussed in order to underline the idea that there is a link between the inverse cascade and trajectory trapping. The physical mechanisms are different in fluids and plasmas due to the different types of nonlinearities of the two systems, but trajectory trapping has the main role in both cases.